Selective Nerve Root Block versus Caudal Epidural Block in Single-Level Lumbar Intervertebral Disc Prolapse - Dr. Narendra Kumar; Dr. Siddhartha Shankar Basumatary; Dr. Mohit Kumar Patralekh; Dr. Deepak Kumar Sharma; Dr Brandon Eric Dkhar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Chronic lumbar radiculopathy due to intervertebral disc prolapse is prevalent and causes significant morbidity. Interventional pain management techniques like Selective Nerve Root Block (SNRB) and Caudal Epidural Block (CEB) are commonly used when conservative treatments fail. This study compares the efficacy of SNRB and CEB in managing pain and improving function in patients with single-level lumbar disc prolapse. Methods: Sixty-six patients with single-level lumbar disc prolapse-induced radiculopathy were assigned according to surgeons choice to receive either SNRB or CEB. Pain intensity was measured using the Visual Analog Scale (VAS), and functional disability was assessed using the Oswestry Disability Index (ODI) and the Roland-Morris Disability Questionnaire (RMDQ) at baseline, 3 weeks, 6 weeks, 3 months, and 6 months post-intervention. Statistical analyses compared outcomes between the two groups. Results: Both SNRB and CEB groups showed significant reductions in VAS, ODI, and RMDQ scores over time (p < 0.001). However, no statistically significant differences were observed between the groups at any follow-up point (p > 0.05). The mean age and sex distribution were comparable between groups (p > 0.05). Conclusion: Both SNRB and CEB are effective in reducing pain and improving function in patients with single-level lumbar disc prolapse. No significant difference was observed between the two interventions over six months, suggesting that either technique can be utilized based on clinical judgment and patient preference.